Internalisasi Nila-Nilai Tauhidullah Pada Pendidikan Sekolah Dasar - Jaelani Salat, Riyan; Qori Amarullah, Risal (Khidmatussifa: Journal of Islamic Studies, 2024)
This research is a qualitative study that aims to analyze the process of internalizing tauhidullah values in the context of education in elementary schools. This study takes a library research approach, namely by analyzing and synthesizing relevant literature that has been previously published. The focus of this research is to understand how education in elementary schools can contribute to shaping students' understanding and awareness of monotheism, the concept of the oneness of God in Islam. Through the collection and analysis of literature carried out, this study identified various approaches and strategies used in elementary school education to internalize the values of tauhidullah. Factors such as curriculum, teaching methods, the role of the teacher, and the school environment have an important role in shaping students' perceptions and appreciation of the concept of tauhidullah. In addition, the literature also reveals challenges and obstacles that may arise in an effort to internalize the values of tauhidullah, such as differences in cultural backgrounds, social environment, and the influence of modern media. The results of the literature analysis show the need for a holistic approach that includes cognitive, affective, and psychomotor aspects in the education of tauhidullah values. Good integration is needed between the religious curriculum, creative and interactive learning approaches, and the active role of the teacher in guiding students in understanding and living the concept of tauhidullah in everyday life.